Characterization of an Ecdysteroid-Regulated 16 kDa Protein Gene in Chinese Oak Silkworm, Antheraea pernyi (Lepidoptera: Saturniidae). Issue 3 (12th May 2020) - Chen, Miao-Miao; Zhong, Liang; Zhao, Chun-Shan; Wang, Feng-Cheng; Ji, Wan-Jie; Zhang, Bo; Liu, Shu-Yu; Liu, Yan-Qun; Li, Xi-Sheng
Abstract: A large number of ecdysteroid-regulated 16 kDa proteins (ESR16s) of insects have been isolated and annotated in GenBank; however, knowledge on insect ESR16s remain limited. In the present study, we characterized an ecdysteroid-regulated 16 kDa protein gene isolated in Chinese oak silkworm, Antheraea pernyi Guérin-Méneville (' ApESR16 ' in the following), an important silk-producing and edible insect. The obtained cDNA sequence of ApESR16 is 1, 049 bp, harboring an open reading frame of 441 bp that encodes a polypeptide of 146 amino acids. CD-search revealed that ApESR16 contains the putative cholesterol/lipid binding sites on conserved domain Npc2_like (Niemann–Pick type C-2) belonging to the MD-2-related lipid-recognition superfamily. Sequence comparison revealed that ApESR16 exhibits 51–57% identity to ESR16s of lepidopteran insects, 36–41% identity to ESR16 or NPC2a of nonlepidopteran insects, and 28–32% identity to NPC2a of vertebrates, indicating a high sequence divergence during the evolution of animals. Phylogenetic analysis found that the used sequences were divided into two groups corresponding to vertebrates and invertebrates, and the used insect sequences were also well clustered according to their families. The A. pernyi ESR16 mRNA is expressed during all four developmental stages and in all tested tissues. Injection of 20-hydroxyecdysone (20-E) into A. pernyi diapausing pupae triggering diapause termination induced upregulation of ESR16 mRNA compared to the diapausing pupae, with the highest expression level at day 2 in the ovaries but day 12 in the fat body. Our results suggested that ApESR16 might be a diapause-related gene and plays a vital role in the pupal diapause of A. pernyi .